Infectious Hypodermal and Hematopoietic Necrosis Virus Detection in Shrimp Farming Pond Sediments - Ruoxuan LÜ; Xiuhua WANG; Meifeng WANG; Xinyu LIAN; Chen LI; Hua XU; Weili YIN; Peng JIA; Bing YANG (Progress in Fishery Sciences)
Infectious hypodermal and hematopoietic necrosis virus (IHHNV) is a shrimp disease that poses a substantial threat to the shrimp farming industry. Owing to the significant economic impact of IHHNV on the global shrimp farming industry, the World Organization for Animal Health (WOAH) has listed IHHNV as a notifiable crustacean pathogen. The primary IHHNV detection method usually involves capturing individual shrimp for molecular biological testing. Using environmental DNA (eDNA) technology, which allows rapid and economical pathogen monitoring directly from environmental samples, has rapidly developed for aquatic animal pathogen detection applications. eDNA is used to detect aquatic pathogens, such as external parasites in fish and crustacean diseases, including white spot syndrome virus (WSSV), Enterocytozoon hepatopenaei (EHP), and IHHNV. For instance, for a method has been developed for detecting Cyprinid herpesvirus 3 (CyHV-3) in environmental waters using virus concentration methods and TaqMan polymerase chain reaction (PCR). The concentration-PCR method achieved an average concentration recovery rate of 67.11% for IHHNV detection in environmental waters based on eDNA principles and techniques. Shrimp carrying the IHHNV pathogen can spread the disease to healthy populations, inducing epidemics. Monitoring pathogens in the water environment is a more direct and effective method compared with testing cultivated shrimp for biosecurity investigations and risk assessments. While such eDNA methods are well-studied, research regarding such applications for soil and sediment is limited. Viruses can persist in pond soil and sediments, serving as natural virus reservoirs and providing potential pathways for virus transmission. However, no studies have monitored the presence of IHHNV in natural environment sediments, which is accompanied by a lack of reliable detecting and quantifying IHHNV detection methods for environmental sediments. eDNA methods enable an effective understanding of pathogen transmission mechanisms and the timely establishment of control measures during disease outbreaks. As a promising tool, eDNA detection has significant application prospects in monitoring aquatic animal diseases. This study aimed to evaluate the effectiveness and feasibility of using eDNA technology to detect the shrimp disease pathogen, IHHNV. Different particle size substrates of pond sediments were selected as study subjects. Extraction conditions were optimized using three commercial kits to evaluate the eDNA extraction effects under different substrates and to detect the lowest nucleic acid detection limit of IHHNV using real-time fluorescent quantitative PCR (RT-qPCR). To verify nucleic acid extraction effectiveness from sediments, three different kits were applied to extract DNA from shrimp tissue in both mud and sand substrates, followed by PCR amplification. Considering factors such as kit price, extraction effect, and duration, Kit B and A were selected for nucleic acid extraction from sand and mud sediments, respectively. RT-qPCR amplification of IHHNV in two types of substrate sediments at different addition volumes were observed. As the addition volume of IHHNV-containing shrimp tissue homogenate decreased, the viral load of IHHNV decreased accordingly. The minimum detectable addition volume for IHHNV in sand sediments was 5 μL, with a viral load of 1.52×102 copies/μL; whereas the minimum detectable addition was 10 μL for mud sediments, with a viral load of 1.32×102 copies/μL. The original viral load in 5 μL and 10 μL homogenate volumes were 9.94×102 and 1.72×103 copies/μL, respectively. Compared to the original viral load added, the recovery rate in sand and mud sediments were approximately 15.30% and 7.70%, respectively. The minimum detection limit concentration of different pond sediment components varied by less than an order of magnitude, showing no significant difference in extraction effects, making it suitable for IHHNV detection in sediments. The optimized eDNA technique and RT-qPCR method for cultured shrimp tissue samples were applied to investigate the presence of IHHNV in the farming environment. IHHNV positives were detected in both sediment and shrimp farming ponds between July and September; however, the positive detection rate was lower in sediment than in shrimp (Penaeus vannamei). The study demonstrates that the detection results of pond sediments and cultured P. vannamei samples are consistent, indicating that pond sediments effectively reflect the IHHNV infection status of shrimp farms. IHHNV RT-qPCR detection in pond sediments during the cultivation period from July to September 2022 were observed. IHHNV loads reached 102 copies/μL level in all six farming ponds. Notably, the IHHNV load in the sediment of pond 6-1 reached up to 4.88×102 copies/μL. Viral loads in shrimp tissue samples reached up to 102–103 copies/μL, indicating that IHHNV loads in shrimp tissue samples were higher than those in pond sediments. This study provides a reliable technical method to evaluate IHHNV detection methods in shrimp farming pond sediments, offering a scientific basis for monitoring the health status of cultured animals and supporting the application of eDNA methods for monitoring shrimp pathogens.